Juvenile arthritis: current concepts in terminology, etiopathogenesis, diagnosis, and management. Issue 7 (July 2016) - Abramowicz, S.; Kim, S.; Prahalad, S.; Chouinard, A.F.; Kaban, L.B.
Abstract: The latest change in terminology from juvenile rheumatoid arthritis (JRA) to juvenile idiopathic arthritis (JIA), established by the International League of Associations for Rheumatology (ILAR), has resulted in some confusion for OMFS and other treating clinicians. JIA comprises a group of systemic inflammatory diseases that result in the destruction of hard and soft tissues in a single or multiple joints. In a significant number of patients, one or both temporomandibular joints (TMJ) are also involved. TMJ disease may be accompanied by pain, swelling, and limitation of motion, as well as mandibular retrognathism, open bite, and asymmetry. The purpose of this article is to provide a review, for the oral and maxillofacial surgeon, of the terminology, etiopathogenesis, diagnosis, and management of children with JIA.